THE ROLE OF THE COMPETITOR IN THE FORMATION OF THE ATHLETE’S PERSONALITY - RAXIMOV M.M. («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
Success in competition depends not only on sports technique, but also on the athlete’s training system, his spiritual views, which show how to program and predict his future sporting achievements, as well as ways to improve results.